Quasi-static and fatigue performance of Ti-6Al-4V triply periodic minimal surface scaffolds manufactured via laser powder bed fusion for hard-tissue engineering - Ragul Gandhi; Lorenzo Pagliari; Riccardo Gerosa; Franco Concli (Results in Engineering)
Additive manufacturing of Triply Periodic Minimum Surface scaffolds offers a promising solution for bone defect restoration and an alternative to traditional implants in hard tissue engineering. This study investigates the quasi-static and tension-compression cyclic properties of laser powder bed fusion-produced Ti6Al4V lattice-based architectures, specifically gyroid and diamond scaffold geometries. The scaffolds were designed to emulate the mechanical properties of bones, with pore sizes (650–1000 μm) suitable for tissue engineering, and porosities ranging from to 30–60 %. The quasi-static tensile properties of the stiffness and yield strength were characterized experimentally and validated numerically using the finite-element method. The results showed that the stiffness and tensile strength of the scaffolds were comparable to those of cortical bone, reducing the risk of scaffold failure. The influence of post-processing by heat treatment and hot isostatic pressing resulted in an increased fatigue limit and ductility compared with non-treated materials reported in the literature. Fractography analysis revealed that fatigue fracture initiation occurred at the outer surface of the skeleton structures, where the maximum tensile stress was concentrated. These findings support the assumption that the designed scaffolds accurately replicate the mechanical and fatigue characteristics of cortical bone, offering suitable alternatives for bone replacement and orthopedic implants.